Evaluation of jet engine operation parameters using conventional and alternative jet fuels. (5th November 2019) - Yakovlieva, Anna; Boichenko, Sergii; Lejda, Kazimierz
Jet engine operation parameters using conventional and alternative jet fuels, obtained by blending with plant oil bio-additives, during bench tests were evaluated. Jet fuels were tested and compared in conditions of engine operation. It was determined that using alternative jet fuels improves jet engine thrust characteristics and reduces fuel flow. These provide more energy efficient operation of jet engine. Using alternative jet fuels results in reduction of gas temperature in the jet pipe. This contributes to durability of materials and structure of the engine against high temperature, as well as reducing of NOx emissions. The results of the study show that operational parameters of the jet engine powered with new alternative jet fuels completely satisfy exploitation norms set in specification for tested engine. Alternative jet fuels, proposed in the study, may be used as a working body of the jet engine without a need of making changes in its design.